To compare the effect of the local delivery of hyaluronan as an adjunct to scaling and root planing versus scaling and root planing alone in the treatment of chronic periodontitis - Srishti Anil Shah; Harshad Narayan Vijayakar; Silvia Victor Rodrigues; Chirag Javerchand Mehta; Dipika Kalyan Mitra; Rohit Ajay Shah (Wolters Kluwer Medknow Publications, 2016)
Background: Hyaluronan is a critical component of the extracellular matrix and contributes significantly to tissue hydrodynamics and cell migration and proliferation. Studies have demonstrated its anti-inflammatory, antibacterial, and regenerative effects. The present study aimed to assess the clinical effects of the subgingival application of 0.8% hyaluronic acid gel as an adjunct to scaling and root planing (SRP) in the treatment of generalized chronic periodontitis. Materials and Methods: Patients with chronic periodontitis were recruited to participate in a study with a split-mouth design and provided informed consent. One hundred sites were included in the study and divided into fifty test sites and fifty control sites. These were assessed for plaque index (PI), gingival index (GI), pocket probing depths, and relative attachment level (RAL) at-pretreatment (baseline), 4, and 12 weeks posttreatment. The patients received full-mouth SRP. A 0.8% hyaluronan gel was administered subgingivally in the test sites at baseline and after 1 week. Significant differences between test and control were evaluated using the t-test, analysis of variance (test) followed by Bonferroni post hoc test. Results: A significant reduction in PI and GI was observed in both groups at 12 weeks (P < 0.05). Significant reduction in the pocket probing depths and gain RAL was observed in both the groups as compared to baseline (P < 0.05). The hyaluronan group compared to control at 12 weeks showed statistically significant reduction in the probing pocket depth and gain in RAL (P < 0.05). Conclusion: The subgingival application of 0.8% hyaluronan gel in conjunction with SRP may have a beneficial effect on periodontal health in patients with chronic periodontitis.